Ubi Jalar Ungu Meningkatkan Kadar Hemoglobin Ibu Hamil Trimester III dengan Anemia - Sandra GJ Tombokan; Freike S.N Lumy; Indah Dwi P. Rono; Wahyuni Wahyuni (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background. Anemia in pregnancy occurs due to pregnancy continuity disorders such as abortion, immature / premature parts. Sweet potatoes contain 4mg of iron in its 100 grams, and can be consumed by pregnant women to increase hemoglobin levels in red blood cells as well as prevent and treat anemia because it is rich in iron. Purpose. This study aims to find out the influence of purple sweet potato consumption on the hemoglobin levels of Pregnant Women trimester III. Method. This type of research uses quasi experimen with Pretest-Posttest Design with Control Group. Total Sampling technique. The study sample of third trimester pregnant women amounted to 30 respondents, consisting of 2 groups, 15 samples of intervention groups and 15 samples of control groups. Result. The results of the study using the Paired t-test test obtained the average hemoglobin level of the pre-test Intervention group of 9.72 and post-test 12.22 then the pre-test Control group of 9.68 and post-test 10.29. The results of the bivariate analysis using an independent t-test sample showed that there was a significant influence between the consumption of purple sweet potatoes on the increase in hemoglobin levels of pregnant women in the third trimester. Conclusion. sweet potato Purple can be used as an alternative food in increasing hemoglobin levels and preventing anemia. Midwives can also encourage pregnant women in addition to consuming Fe tablets, can consume other foods containing iron, one of which is by consuming purple sweet potatoes.